Human Capital Analysis Affects Economic Growth - Veronika Nugraheni Sri Lestari; Dwi Cahyono; Nikolai Rezky Miftahurrachman (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This study focuses on finding out whether human capital, which is an indicator of the quality of human resources, has a significant effect on economic growth. This study uses several indicators, including life expectancy, literacy, consumption, and the average length of schooling. One of the inhibiting factors for economic growth is poverty, so that the Government has implemented various programs aimed at alleviating poverty. This is quantitative research. The data used is secondary data obtained from the Central Statistics Agency (BPS) of East Java Province. The data obtained includes life expectancy, per capita consumption, average length of schooling, literacy rates, poverty, and economic growth in East Java during the 2010-2015 period. The results showed that Life Expectancy, Per capita Consumption, Average Length of Schooling, and Poverty had no significant effect on economic growth in East Java Province. However, literacy rate had a significant effect on economic growth in East Java during the 2010-2015 period.